Biosorption of Cr(III) from aqueous solution using an agricultural by-product jute stick powder: Equilibrium and kinetic studies - Uddin, Mohammad Nasir; Alam, Jahangir; Naher, Syeda Rahimon (European Journal of Chemistry, 2018)
The adsorption capacity of chromium(III) from synthetic waste water solution by a low cost biomaterial, Jute Stick Powder (JSP)was examined. A series of batch experiments were conducted at different pH values, adsorbent dosage and initial chromium concentration to investigate the effects of these experimental conditions. To analyze the metal adsorption on to the JSP, most common adsorption isotherm models were applied. To study the reaction rate, the kinetic and diffusion models were also applied. The morphological structure and variation of functional groups in the JSP before and after adsorption was examined by scanning electron microscope (SEM) and Fourier transform infrared spectrometry (FT-IR). Maximum chromium removal capacities of JSP was 84.34%with corresponding equilibrium uptake 8.4 mg/g from 50 mg/L of synthetic metal solution in 60 minutes of contact time at pH = 6.0 and 28 °C with continuous stirring at 180 rpm. The percent sorption of the biomass decreased with increasing concentration of metal ion but increased with decreasing pH, increasing contact time and adsorbent doses. Data for this study indicated a good correspondence with both isotherms of Langmuir and Freundlich isotherm. The analysis of kinetic indicated that Chromium was consistent with the second-order kinetic adsorption model. The rate of removal of Cr(III) ions from aqueous solution by JSP was found rapid initially within 5-30 minutes and reached in equilibrium in about 40 minutes. The investigation revealed that JSP, a low cost agricultural byproduct, was a potential adsorbent for removal of heavy metal ions from aqueous solution.